A Discourse Analysis of news reports on farm murders in South Africa - Ntantala, Noxolo (University of the Witwatersrand, Johannesburg, 2024)
Farm murders in South Africa represent more than isolated incidents of violence, they are symptomatic of deeper societal issues, including socioeconomic disparities and historical injustices. Addressing farm murders requires a nuanced understanding of their broader implications and the underlying power dynamics shaping public discourse surrounding these crimes. Critical Discourse Analysis (CDA) offers a valuable lens through which to examine media representations of farm murders. By scrutinizing language use in media discourse, CDA enables researcher to uncover the ways in which power structures and ideological biases influence public perceptions and societal norms (Fairclough, 1995). This analytical approach is particularly apt for studying farm murders, as it allows for the exploration of how media narratives frame these crimes within the socio-political landscape of South Africa. In this research, I have conducted a Critical Discourse Analysis of media representations of farm murders, utilizing Fairclough’s three-dimensional model as my theoretical framework to analyse18 newspaper articles from prominent outlets spanning from the year 2017 to 2023, including The Citizen, Sunday Independent, Cape Argus, Pretoria News Weekend, Diamond field Advertiser and Daily News. The aim was to elucidate how these articles construct and frame the discourse surrounding farm murders. By critically analyzing the language and narratives employed in media coverage, my study sheds light on the underlying power dynamics and ideological influences shaping public perceptions of farm murders. This research unveils media portrayal of farm murders in South Africa, highlighting prevalent direct quotations and sensationalized narratives. While emphasizing farmers’ innocence and law enforcement responsiveness, media disproportionately focuses on victims over perpetrators. These portrayals evoke fear and sympathy, prompting discussions on community cohesion and broader societal impacts
A research report Submitted in fulfillment of the requirements for a Master of Arts , In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Critical Discourse Analysis; Farm murders; Newspaper; Violent crime; SDG-8: Decent work and economic growth